Case report: A unusual case of delayed propionic acidemia complicated with subdural hematoma - Jiang, Zongzhi; Fu, Yuxin; Wei, Xiaojing; Wang, Ziyi; Yu, Xuefan (Frontiers in Neurology, 2022)
Background Propionic acidemia (PA) is an inherited autosomal recessive metabolic disorder that is classified as early-onset or late-onset, depending on the onset time of clinical symptoms. It clinically manifests as numerous lesions in the brain, pancreas, liver, and muscle. Muscle biopsies show myopathic changes, which help to distinguish late-onset propionic acidemia from other metabolic diseases involving muscles. Case presentation A 19-year-old Chinese girl was admitted to the hospital because of poor eating and fatigue. Head magnetic resonance imaging suggested metabolic diseases, and we administered symptomatic support treatment. Her symptoms gradually worsened, and she began to show convulsions and disturbances of consciousness. Muscle pathology showed myopathy-like changes. The presence of organic acids in the blood and urine suggested PA. Genetic analyses identified two compound heterozygous mutations in the patient's PCCB gene, confirming the diagnosis of delayed PA. Conclusions The muscle pathological examination of late-onset PA provides valuable information that is helpful for distinguishing delayed-onset PA from metabolic diseases. In the absence of a history of trauma, subdural hematoma may be a very rare complication of late-onset PA and can be regarded as a poor prognostic sign; therefore, it is suggested to perform head computed tomography as part of the routine neurological evaluation of PA patients.